WITNESS PROTECTION PROGRAMME: THE VIEWS OF WITNESSES AND STAFF MEMBERS ON HOW CHILDREN ARE AFFECTED BY THE ADMISSION OF THEIR PARENTS INTO THE PROGRAMME - Mphaphuli, Lucy Nthepa (Social Work/Maatskaplike Werk, 2022)
Children, although innocent, are often admitted into the witness protection programme with their parents and, as a result, they experience isolation and social uprooting. This qualitative study aimed to describe the views of witnesses and staff members on how children are affected by the admission of their parents into the witness protection programme in South Africa. The ecological systems perspective, which recognises the impact of the environment on human functioning, and the person-in-environment perspective provided the theoretical framework. The findings confirmed the hardships of children in coping with the admission of their parents into the witness protection programme.